Peran Dinas Sosial dalam Menanggulangi Eksploitasi Anak Jalanan di Kota Surabaya - Puri, Aninda; Hertati, Diana (Universitas Muhammadiyah Sorong, 2024)
This research aims to determine and analyze the role of the Surabaya City Social Service in overcoming the exploitation of street children in the City of Surabaya, the factors that cause child exploitation and the obstacles and challenges faced by the Surabaya City Social Service. The method used is qualitative field research with a descriptive type of analysis. Data collection is carried out by means of interviews which are the primary data source and observations as well as documents, reports and others become secondary data. The informants chosen are people who have the capacity to answer the author's questions. The research results show that the role of the City Social Service consists of a facility role, an educational role, a representational role and a technical role. Then the cause of child exploitation in the city of Surabaya is due to behavioral illnesses that individuals and groups have become accustomed to. This habit occurs because there is no special role to eradicate this case and the weakness of the legal domain. Apart from that, the profits obtained from busking and begging are more attractive than working at a food court all day and night. The obstacles and challenges faced by the Surabaya City Social Service include weak law enforcement processes, domicile status, unavailability of infrastructure and lack of skilled personnel.